A synthetic indicator of corruption for Latin America: a global vision. Issue 2 (19th March 2018) - Cardenas Cardenas, Gilberto; García Gamez, Sofía; Salas Suarez, Alvaro
Abstract : Purpose: The purpose of this paper is to develop an overview of the phenomenon of corruption in Latin America and to propose a synthetic aggregate indicator to compress most of the statistical information available on corruption for Latin American countries. Design/methodology/approach: The indicator of corruption has been obtained through factor analysis by applying the principal component methodology. Findings: The authors have managed to obtain a single component that reproduces and synthesizes 86 per cent of all the information about corruption in Latin America gathered by prestigious institutions. Research limitations/implications: The authors are aware that their study is not free from limitations. The first limitation is associated with the impossibility of incorporating information related to the phenomenon of corruption from the indicator called Latinobarómetro, as the economies of Cuba and Haiti (included in this research) are not part of the sample analyzed by that indicator. Second, this study reproduces and synthesizes 86 per cent of all available information by prestigious institutions about corruption in Latin America, and although this percentage is significant, it does not constitute 100 per cent. Originality/value: This study has created a new indicator that gathers methodologies to measure corruption in Latin American countries.